2016
DOI: 10.1007/s40262-016-0444-x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences in Serotonin Transporter Occupancy by Escitalopram: An [11C]DASB PK-PD Study

Abstract: Higher doses of escitalopram than 20 mg are needed to achieve 80 % or greater SERT occupancy. Higher occupancy by escitalopram in the dorsal raphe nucleus relative to the striatum may explain the delayed onset of action of SSRIs by modulating autoreceptor function. The prevention of the 5-HT autoreceptor-mediated negative feedback could be a strategy for accelerating the clinical antidepressant effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…The mice were coadministered with 5 mg/kg doses of S-Cit and Alk-S-Cit, and their brain sections were collected after 1 hour. Previous PET studies have shown that the occupation of SERT by S-Cit is high in the dorsal raphe nucleus and striatum (5). S-Cit and Alk-S-Cit were detected in the homogenate of the 0.5 mm-thick brain sections, including the dorsal raphe nucleus and the striatum, at different retention times (1.04 and 1.44 minutes, respectively; Figure 2, B and C).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The mice were coadministered with 5 mg/kg doses of S-Cit and Alk-S-Cit, and their brain sections were collected after 1 hour. Previous PET studies have shown that the occupation of SERT by S-Cit is high in the dorsal raphe nucleus and striatum (5). S-Cit and Alk-S-Cit were detected in the homogenate of the 0.5 mm-thick brain sections, including the dorsal raphe nucleus and the striatum, at different retention times (1.04 and 1.44 minutes, respectively; Figure 2, B and C).…”
Section: Resultsmentioning
confidence: 77%
“…Therefore, our multimodal imaging technique is an effective method for detecting low-molecular weight compounds in their original tissue environment and can potentially offer additional information regarding the precise spatial distribution of such drugs. and frontal cortex, as compared with the hippocampus and putamen, although at a resolution on the millimeter order (3)(4)(5). Alternatively, MSI techniques coupled with matrix-assisted laser desorption/ionization or desorption electrospray ionization (DESI) allow for the direct determination of nonlabeled drug distributions at improved resolutions (6).…”
Section: Introductionmentioning
confidence: 99%
“…We contacted the authors of 12 articles to obtain missing data, four of whom were able to provide the requested data [ 31 , 33 , 35 , 38 ] (previously unreported data is marked (†) in the tables).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies excluded participants taking other possibly interacting medications (e.g., other psychotropic drugs or substances with high affinity for SERT) [ 19 , 31 , 32 , 37 40 , 42 ]. A fasting regimen was mentioned in one study [ 35 ]: requiring a minimum of 4 h fasting prior to imaging. Two studies mentioned having standardized the time of day of drug administration and scanning [ 19 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation